2014
DOI: 10.1111/imm.12320
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhimurium immunotherapy for B‐cell lymphoma induces broad anti‐tumour immunity with therapeutic effect

Abstract: SummaryDespite the efficacy of current immune-chemotherapy for treatment of Bcell non-Hodgkin lymphoma, a substantial proportion of patients relapse, highlighting the need for new therapeutic modalities. The use of live microorganisms to develop anti-tumoural therapies has evolved since Coley's toxin and is now receiving renewed attention. Salmonella Typhimurium has been shown to be highly effective as an anti-tumour agent in many solid cancer models, but it has not been used in haematooncology. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 42 publications
4
68
0
Order By: Relevance
“…We have previously assessed a murine NHL-B model where different immunotherapies were evaluated with promising results [1012]. In the present study, we establish a new NHL-B pre-clinical model using standard chemotherapy (CHOP) to achieve complete response in immunocompetent animals.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously assessed a murine NHL-B model where different immunotherapies were evaluated with promising results [1012]. In the present study, we establish a new NHL-B pre-clinical model using standard chemotherapy (CHOP) to achieve complete response in immunocompetent animals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a recent related study of our group has shown that i.t. administrations of Salmonella LVR01 generate a considerable dose-dependent antitumor effect in a mouse model of B-cell lymphoma [ 42 ]. Despite this result, when two doses of LVR01 were inoculated into primary 4T1 tumors, no survival improvement was seen in tumor-bearing animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our neoadjuvant approach is based on the use of IL-12, a potent immunostimulatory cytokine with strong antiangiogenic activity [ 32 , 35 , 43 ] in combination with LVR01, an attenuated auxotrophic mutant of S . Typhimurium [ 27 , 42 ] as co-adjuvant factor. To allow IL-12 expression into the tumor mass we employed a SFV-based vector encoding IL-12 genes (SFV-IL-12), which was previously shown to express IL-12 (locally and systemically) upon i.t.…”
Section: Discussionmentioning
confidence: 99%
“…B‐cell lymphomas demonstrate inter‐play between tumor and the host immune system that appears to directly affect lymphoma growth. This is supported by their ability to undergo spontaneous regression, their reported response to non‐specific immune activators such as infectious triggers, and their response to B cell‐directed monoclonal antibodies . Furthermore, some B‐cell malignancies, such as follicular lymphoma, contain many tumor‐infiltrating lymphocytes in the tumor microenvironment that are potential candidates for checkpoint blockade to elicit local immune activation against malignant B cells.…”
Section: Efficacy Of Immune Checkpoint Blockade In Lymphoid Malignancymentioning
confidence: 99%